A contribution to the synsedimentary versus epigenetic origin of the Cu mineralizations hosted by terminal Neoproterozoic to Cambrian formations of the Bou Azzer–El Graara inlier: New insights from the Jbel Laassel deposit (Anti Atlas, Morocco). (July 2015) - Bourque, H.; Barbanson, L.; Sizaret, S.; Branquet, Y.; Ramboz, C.; Ennaciri, A.; El Ghorfi, M.; Badra, L.
Highlights: Copper mineralization occurs in a Variscan folding band in Cambrian cover. The mineralization appears as a stockwork with autosimilar texture. Results from component principal analyses do not show relation with lithology. The Cu-mineralization is epigenetic, controlled by fold axis. Abstract: The Neoproterozoic to Cambrian formations that compose the cover of the Bou Azzer–El Graara inlier, host a great number of Copper occurrence whose origin is largely discussed. To bring some light to this debate, structural, petrographic and geochemical observations were performed on the copper deposit of Jbel Laassel. This deposit, located at the extreme ESE of the Bou Azzer–El Graara inlier, is mined since 2012. At the district scale, the ore bodies localize in a folding band that extends along a NE–SW direction. At macroscopic, microscopic and scanning electron microscope scales the mineralization appears as banding veins, with locally cockade breccia and comb quartz textures. From the macroscopic scale to the scale of the scanning electron microscope, all these mineralized textures are connected there between forming a stockwork with an auto-similar structure in the range of used scales of observation. At the district scale, this stockwork is preferentially located in the anticlinal hinges of the folding band. Principal component analyses of geochemical database enable to distinguish several groups of chemical elements, each of these groups corresponding to the different lithologies and to the copper mineralization. This last group does not show any correlation with the distinguished lithological groups. All these observations bring new arguments to an epigenetic origin for the copper mineralization of the Jbel Laassel deposit, with a formation contemporary or posterior with the folding band development attributed to Variscan deformation.